Use of E-Resources by the Faculty Members with Special Reference to CVRCE, Bhubaneswar - Satpathy, Sunil Kumar; Rout, Biswanath (DESIDOC Journal of Library & Information Technology, 2010)
This paper aims to assess and evaluate the use of e-resources by the faculty members of C.V. Raman College of Engineering (CVRCE), Bhubaneswar, with a view to examine the exposure of faculty members to e-resources. Besides, it aims to highlight the problems encountered by the users and suggests some remedial measures for its improvement. The authors investigate the use of e-resources by the faculty members of CVRCE through a survey based on a structured questionnaire. Various statistical methods have been used for data analysis. The study confirmed that faculty members are aware of the e-resources and various types of e-resources, e-database, and e-journals. It suggests for the improvement in the access facilities with high Internet speed and subscription to more e-resources by the Central Library of CVRCE. DOI: 10.14429/djlit.30.455